Scapholunate dissociation; diagnostics made easy. Issue 92 (July 2017) - Cheriex, K.C.A.L.; Sulkers, G.S.I.; Terra, M.P.; Schep, N.W.L.; van Aard, B.J.P.L.; Strackee, S.D.
Abstract: Scapholunate dissociation (SLD) is a form of carpal instability, caused by rupture of the scapholunate ligament (SLL) the secondary stabiliser of the scapholunate (SL) compartment. SLD can cause osteoarthritis of the wrist. Recently a study was published that shows cineradiography to be an excellent radiological imaging technique for diagnosing SLD at a tertiary centre for hand and wrist surgery [1]. As the quality of these results can be influenced by the expertise of the operator and observer of the cineradiographic studies, the aim of this study was to determine if these results were reproducible at a secondary centre for hand and wrist surgery with less expertise in wrist cineradiography. All cineradiographic studies carried out during a 10-year period were obtained. All patients who underwent the gold standard procedure (arthroscopy/arthrotomy) after cineradiography were included, a total of 50 patients. The diagnostic accuracy of detecting SLD by both cineradiography and conventional radiography was calculated. Cineradiography had a high diagnostic accuracy, while the accuracy for conventional radiography was average. When all wrists with an SL distance ≥3 mm were excluded (static SLD), diagnostic accuracy for conventional radiography dropped even lower, while accuracy for cineradiography remained high. These results are comparable with published accuracy rates and show that cineradiography has a high diagnostic value for detecting SLD and do not seem to be influenced by the operator or observer of the cineradiographic studies.